THE RELATIONSHIP OF THE AGE OF PREGNANT MOTHERS IN TRIMESTER III TO THE EVENT OF PREECLAMSIA IN BANGIL HOSPITAL, PASURUAN REGENCY - Aksari, Jumita (Rena Cipta Mandiri, 2022)
The maternal mortality rate (MMR) in Indonesia is still high at 305 per 100,000 live births. The direct cause of maternal death related to pregnancy and childbirth is preeclampsia (24%), the age of pregnant women 20 years or 35 years has a risk of 3.144 times (Ministry of Health, 2014) ). Objective: To analyze the relationship between the age of pregnant women in the third trimester of the incidence of preeclampsia in Bangil Hospital, Pasuruan Regency. Methods: An analytical observational study with a cross sectional type by taking accidental sampling technique. The independent variable of the study was the age of the third trimester of pregnant women. The research instrument used an interview sheet. Statistical test with Chi Square. Result: Chi-Square calculation test analysis obtained the Asymp value. Sig of 0.000 <0.05 and x² count 14,441 > x² table 107.52 which means Ha is accepted and Ho is rejected with a significant relationship level = 0.05 (value x² count > x² table). Conclusion: there is a relationship between the age of pregnant women in the third trimester of the incidence of preeclampsia in Bangil Hospital, Pasuruan Regency.